2023
DOI: 10.1111/jace.19166
|View full text |Cite
|
Sign up to set email alerts
|

Flash in argon atmosphere yields electronically conducting yttria‐stabilized zirconia at ambient temperature

Abstract: This is the second report on the retention of electronic conductivity in yttriastabilized zirconia at room temperature after cooling down from the state of flash . In the first report, the specimens (which were flashed in air) were quenched by in-flash immersion into liquid nitrogen. Now we show that if the specimens are flashed in Ar in a glove box (O 2 < 1 ppm), then they remain electronic conductors under nominal cooling. Indeed, the conductivity of the Ar-flashed specimens is higher than the conductivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…The in-operando interface resistance at the anode and the cathode, from both Ar and air experiments, measured by the four-point method, is reproduced in Figure S2. 10…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in-operando interface resistance at the anode and the cathode, from both Ar and air experiments, measured by the four-point method, is reproduced in Figure S2. 10…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the specimens flashed in Ar remained electronically conducting. 10 Therefore, the discharge in SO2 occurs solely through the external resistor, while in Ar it occurs via the external resistor and the internal resistance of the specimen, effectively connected in parallel. Therefore, for the case of SAr, the total discharge resistance would have been lower than the external resistance.…”
Section: Capacitor Discharge Measurementsmentioning
confidence: 99%
“…In a recent publication in this journal, Jo et al 1 state: "In a recent paper, 2 Bechteler et al showed that the optical spectra from a graphite furnace heated to 1200 • C also show electroluminescent spectra." We wish to point out that this statement is factually incorrect and that as a consequence, Jo et al seriously misinterpret the scientific implications of our results.…”
mentioning
confidence: 99%
“…The error in the above quotation 1 is that the sample referred to is a freestanding piece of graphite heated to 1200 • C in an alumina tube furnace with external heating elements, as is clearly described in Ref. [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation